Предмет: Алгебра,
автор: iliaBolotov24
3 х-9:х-1+х+6:х+1=4
Приложения:
Ответы
Автор ответа:
0
(3х-9)(х+1)+(х+6)(х-1)
------------------------- =4
(х+1)(х-1)
3х^2+3х-9х-9+х^2-х+6х-6=4 (х+1)(х-1)
4 х^2-х-15=4 ( х^2-1)
4х^2-х-15=4 х^2-4
х=-11
------------------------- =4
(х+1)(х-1)
3х^2+3х-9х-9+х^2-х+6х-6=4 (х+1)(х-1)
4 х^2-х-15=4 ( х^2-1)
4х^2-х-15=4 х^2-4
х=-11
Автор ответа:
0
общ. знаменатель (х-1)*(х+1)
(3х-9)*(х+1)+(х+6)*(х-1)=4*(х+1)*(х-1)
3+3х-9х-9+-х+6х-6=4(-1)
4-х-15=4-4
х=-11
(3х-9)*(х+1)+(х+6)*(х-1)=4*(х+1)*(х-1)
3+3х-9х-9+-х+6х-6=4(-1)
4-х-15=4-4
х=-11
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Қазақ тiлi,
автор: Djakal
Предмет: Алгебра,
автор: ivaska007oxn6mm
Предмет: Математика,
автор: михриб